2016
DOI: 10.3382/ps/pew017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical water bath stunning on physical reflexes of broilers: evaluation of stunning efficacy under field conditions

Abstract: The effects of different amounts and frequencies of stunning sine wave alternating current were investigated under field conditions. Seven hundred and fifty broilers were stunned in an electrical water bath with an average root mean square (RMS) current of 150, 200, and 250 mA and frequencies of 200, 400, 600, 800, and 1,200 Hz. The occurrence of corneal reflex, spontaneous eye blinking, and a positive response to a painful stimulus were monitored and recorded immediately after the stunning and at 20 s post-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…According to the Eu Regulation n. 1099/2009, FBO may use a wide range of frequency values (up to 1500 Hz) and a current intensity, ranging from 100 to 200 mA. FBO may use, therefore, different combinations of electrical parameters in order to safeguard both animal welfare and the possible downgrading of meat minimizing economic losses [ 2 , 8 , 25 , 26 ]. The amount of the current has great importance on stunning efficiency, and it is proven that currents below 100 mA do not reach an adequate level of unconsciousness [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the Eu Regulation n. 1099/2009, FBO may use a wide range of frequency values (up to 1500 Hz) and a current intensity, ranging from 100 to 200 mA. FBO may use, therefore, different combinations of electrical parameters in order to safeguard both animal welfare and the possible downgrading of meat minimizing economic losses [ 2 , 8 , 25 , 26 ]. The amount of the current has great importance on stunning efficiency, and it is proven that currents below 100 mA do not reach an adequate level of unconsciousness [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a low percentage of animals (around 1%) showed signs of stunning ineffectiveness. It has been previously reported that when low intensities are applied, high electrical frequencies are less effective in overcoming impedance in the tissues of the birds leading to a short period of unconsciousness in the animals [ 2 , 22 ]. The outcomes of the present work confirm the efficacy of high frequency combined with the high root mean square current up to 200 mA as already reported by Raj [ 25 ] and Girasole [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more recent study using a multiple‐bird waterbath stunner under slaughterhouse conditions, Girasole et al. () investigated the effectiveness of stunning broilers with average RMS currents of 150, 200 and 250 mA and frequencies of 200, 400, 600, 800 and 1,200 Hz delivered using sinewave AC. Occurrence of the corneal reflex, spontaneous eye blinking, and a positive response to a painful stimulus were monitored and recorded as indicators of consciousness immediately after the stunning and at 20 s post‐stun.…”
Section: Assessmentmentioning
confidence: 99%